Cytokines in Pericardial Effusion of Patients with Inflammatory Pericardial Disease - Karatolios, Konstantinos (Hindawi Publishing Corporation, 2012)
Background. The role of inflammatory and angiogenic cytokines in patients with inflammatory pericardial effusion still remains uncertain. Methods. We assessed pericardial and serum levels of VEGF, bFGF, IL-1β and TNF-α by ELISA in patients with inflammatory pericardial effusion (PE) of autoreactive (n = 22) and viral (n = 11) origin, and for control in pericardial fluid (PF) and serum (n = 26) of patients with coronary artery disease (CAD) undergoing coronary artery bypass graft surgery. Results. VEGF levels were significantly higher in patients with autoreactive and viral PE than in patients with CAD in both PE (P = 0, 006 for autoreactive and P < 0, 001 for viral PE) and serum (P < 0, 001 for autoreactive and P < 0, 001 for viral PE). Pericardial bFGF levels were higher compared to serum levels in patients with inflammatory PE and patients with CAD (P ≤ 0, 001 for CAD; P ≤ 0, 001 for autoreactive PE; P = 0, 005 for viral PE). Pericardial VEGF levels correlated positively with markers of pericardial inflammation, whereas pericardial bFGF levels showed a negative correlation. IL-1β and TNF-α were detectable only in few PE and serum samples. Conclusions. VEGF and bFGF levels in pericardial effusion are elevated in patients with inflammatory PE. It is thus possible that VEGF and bFGF participate in the pathogenesis of inflammatory pericardial disease.